Improving Early Reading Skills Through Picture Storybook-Based Learning - Albertin; Agus Basuki (International Journal of Social Sciences and Humanities, 2026)
This study aimed to: (1) describe the implementation of picture storybook media in beginning reading instruction for first-grade students at SDN 001 Teluk Pandan, and (2) examine the improvement of students' beginning reading skills through the use of this instructional media. The study was motivated by the low level of students' beginning reading skills, as indicated by an initial mean score of 61.50, with all students (100%) failing to achieve the Minimum Learning Achievement Criteria (KKTP) of 75. This study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of four stages: planning, action, observation, and reflection. The participants were six first-grade students at SDN 001 Teluk Pandan, East Kutai Regency, comprising three boys and three girls. The research was conducted over two cycles, with each cycle consisting of two meetings. Data were collected through beginning reading tests, classroom observations, and documentation, and were analyzed using descriptive quantitative techniques based on mean scores and classical learning mastery percentages. The findings revealed that the use of picture storybook media effectively improved students' beginning reading skills. The mean score increased from 61.50 in the pre-cycle to 80.00 at the end of Cycle II, while the classical learning mastery improved from 0.00% to 83.33%, exceeding the predetermined success criterion of at least 75%. Students' learning activities also improved substantially, from 50.00% (fair category) to 92.50% (very good category). Therefore, the use of picture storybook media was found to be effective in improving the beginning reading skills of first-grade elementary school students.